Antibacterial potential of red betel Leaf (Piper crocatum Ruiz & Pav) against Fusobacterium nucleatum ATCC 25586: Potensi antibakteri ekstrak daun sirih merah (Piper crocatum Ruiz & Pav) terhadap Fusobacterium nucleatum ATCC 25586 - Aditya Syahrul Ramadhan; Dian Lesmana; Philips Onggowidjaja (Makassar Dental Journal, 2022)
The micro-organism that affects periodontitis is Fusobacterium nucleatum. To inhibit the growth of these micro-organisms, al-ternative herbal medicines are used, such as red betel leaf extract (Piper crocatum Ruiz & Pav) because it contains tannins, fla-vonoids, and saponins which have antibacterial and anti-inflammatoryproperties. This study was conducted to determine the an-tibacterial potential of RBL against the bacteria F.nucleatum ATCC 25586 using the agar diffusion method (Kirby-Bauer) with chlorhexidine as a positive control, aquadest as a negative control, RBL ethanol extract with concentrations of 10%, 15%, 20%, 25%, and 30%. Replication 3 times, so the total samples are 21 plates. Data were analyzed by one-way Anova using SPSS v.21. The ethanol extract of RBL appeared to have weak inhibition at concentrations of 10% and 15% and strong inhibition at con-centrations of 20%, 25%, and 30% against F.nucleatum ATCC25586. It was concluded that there was a strong antibacterial po-tential of RBL extract against F.nucleatum ATCC 25586 at a concentration of 30%.